2016
DOI: 10.1080/13688804.2016.1196585
|View full text |Cite
|
Sign up to set email alerts
|

Looking for The Illustrated London News in Australian Digital Newspapers

Abstract: This article will demonstrate that digital newspaper archives can be used to shed new light on the historical readership of nineteenth-century newspapers and magazines. The digital newspaper archive of Australia (Trove) was used to study the distribution and reception of the renowned Illustrated London News (ILN) in the Australian colonies between 1842 and 1872. As a result of this research, this article shows that around 17,000 copies of the magazine reached the Australian colonies by each mail in 1862. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We need to be mindful that the convenience of digitisation does not make us lazy press researchers and that we do not allow technology to determine our research agendas. Adrian Bingham (2010: 229) warns that keyword searching can be a blunt instrument; I would add that manual searching has the capacity to bring us serendipitous findings (Akami et al, 2014: 7; Smits, 2017: 94; Wijfjes, c. 2016–2017: 3). Then again, Australian researchers are fortunate that Trove supplies not just the full text of articles, but an image of the whole page (Crabb et al, 2014: 179).…”
Section: From Analogue To Digitalmentioning
confidence: 99%
“…We need to be mindful that the convenience of digitisation does not make us lazy press researchers and that we do not allow technology to determine our research agendas. Adrian Bingham (2010: 229) warns that keyword searching can be a blunt instrument; I would add that manual searching has the capacity to bring us serendipitous findings (Akami et al, 2014: 7; Smits, 2017: 94; Wijfjes, c. 2016–2017: 3). Then again, Australian researchers are fortunate that Trove supplies not just the full text of articles, but an image of the whole page (Crabb et al, 2014: 179).…”
Section: From Analogue To Digitalmentioning
confidence: 99%
“…4 Earlier studies have identified the so called 'scissor-paste' news culture, where circulating textual borrowings had truly made the world smaller by the early twentieth century, simultaneously easing the transfer of culture and influencing the relations of the centres and peripheries of information. 5 Examining the circulation of the dramatic Bobrikov news illustrates the dynamics of news flows such as in the case of unexpected news coming from the relative 'periphery' of the newsworld.…”
mentioning
confidence: 99%
“…Such formations of new communities were identified by scholars in the study of Illustrated London News (ILN)-one of the key pillars of the British imagined community in the 1800s. In the narratives adopted by ILN, most studies identified a clear distinction between the British 'us' and the non-British or non-English 'them' (Sinnema, 1998, McKendry, 1994, Potter, 2003, Lester 2002, Smits, 2017. Sinnema, on the other hand, also identified an 'us vs them' narrative that was rooted in class division.…”
Section: Forming Imagined Communitiesmentioning
confidence: 99%